Case of Pseudo-Bartter's Syndrome: An atypical presentation of cystic fibrosis - khorasani, Enayatollah Nemat (Journal of Nepal Paediatric Society, 2011)
A three months infant who in the beginning had disease cystic fibrosis was diagonosed with pseudo-bartter's syndrome. The disease began with coughing, diarrhoea, vomiting and weakness. Investigation revealed; electrolytes showin hyponatremia (110 mmol/L) and hypokalemic (2.6 mmol/L) and hypochloremic (63 mmol/L) metabolic alkalosis (HCO3=43 mmol/L). Key words: Pseudo Bartter's Syndrome; Cystic fibrosis; Metabolic alkalosis. DOI: 10.3126/jnps.v31i2.3911 J Nep Paedtr Soc 2010;31(2):121-123